An imaginative Whig : reassessing the life and thought of Edmund Burke - Crowe, Ian (University of Missouri Press, 2005)
"Explores the significance of Edmund Burke's eighteenth-century writings on multiculturalism, the impact of postmodern and relativist methodologies, the boundaries of church-state relationships, and religious tolerance by emphasizing his career and his position on historiography, moral philosophy, jurisprudence, and philosophical skepticism"--Provided by publisher